A study on finance-growth nexus in dual financial system countries: evidence from Bahrain - Abduh, Muhamad; Brahim, Said; Omar, Mohd. Azmi (IDOSI Publication, 2012)
This study is aimed at examining the long run and short run relationships between both Islamic and conventional financial development with the economic growth in the Bahrain dual financial system. Using quarterly data (2000:1-2010:4) retrieved from Monthly Statistical Bulletin of Central bank of Bahrain (CBB) and International Financial Statistics (IFS) of International Monetary Funds (IMF), this paper employs the Johanson and Juselius Cointegration test and Vector Error Correction Model (VECM) to uncover the long-run and short-run relationship between Islamic and conventional financial deepening and economic growth. The results show a significant positive relationship between Islamic finance deepening and economic growth in the long run, however, there is no evidence on the short run relationship between them. The Islamic finance relationship with economic growth in Bahrain appears to be a bi-directional relationship. On the other hand, Bahraini conventional finance has a significant relationship with their economic growth, both in the long run and short run.